THE EFFECT OF JUST IN TIME TEACHING (JITT) LEARNING MODEL ON THE CONCEPT MASTERY OF STUDENTS LEARNING MOTIVATION - Ayu, Hena Dian; Sagita, Ulfa; Jufriadi, Akhmad (Jurnal Pengajaran MIPA, 2019)
This study aims to determine the effect of the Just In Time Teaching (JITT) learning model on mastery of concepts in terms of student learning motivation. The design used in the study was quasi experiment. The design of this study used posttest only control group design. Where the study population was class VIII students at SMP Negeri 3 Kepanjen. The instrument used to measure mastery of concepts is a post test question, while measuring motivation for learning is a sheet of observation of learning motivation. The technique for testing hypotheses is to use the Analysis of Variance. The results showed that: 1) there was the influence of mastery of students' concepts taught using just in time teaching learning models, and students taught using conventional learning models, 2) there were differences in mastery of physics concepts of students who were highly motivated with students who had motivation low, 3) there is no interaction between just in time teaching and conventional learning models with learning motivation towards mastery of concepts. Based on the results of the study, it can be concluded that students who learn with the Just In Time Teaching learning model mastery the concept is higher than students who study with conventional learning models. Students who have high learning motivation have higher mastery of concepts compared to students who have low learning motivation. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Just In Time Teaching (JITT) terhadap penguasaan konsep ditinjau dari motivasi belajar siswa. Rancangan yang digunakan dalam penelitian adalah quasi experiment. Desain penelitian ini menggunakan posttest only control group design. Dimana populasi penelitian adalah siswa kelas VIII di SMP Negeri 3 Kepanjen. Instrumen yang digunakan untuk mengukur penguasaan konsep adalah soal post test, sedangkan untuk mengukur motivasi belajar adalah lembar observasi motivasi belajar. Teknik untuk menguji hipotesis adalah dengan menggunakan uji Anova Dua Jalur. Hasil penelitian menunjukkan bahwa: 1) ada pengaruh penguasaan konsep siswa yang diajar menggunakan model pembelajaran just in time teaching, dan siswa yang diajar menggunakan model pembelajaran konvensional, 2) ada perbedaan penguasaan konsep fisika siswa yang mempunyai motivasi tinggi dengan siswa yang mempunyai motivasi rendah, 3) tidak ada interaksi antara model pembelajaran just in time teaching dan konvensional dengan motivasi belajar terhadap penguasaan konsep. Berdasarkan hasil penelitian maka diperoleh kesimpulan bahwa siswa yang belajar dengan model pembelajaran Just In Time Teaching penguasaan konsepnya lebih tinggi daripada siswa yang belajar dengan model pembelajaran konvensional. Siswa yang memiliki motivasi belajar tinggi memiliki penguasaan konsep yang lebih tinggi dibandingkan dengan siswa yang memiliki motivasi belajar rendah.Keywords: Just In Time Teaching (JITT), Mastery of Concepts, Learning Motivation